217k views
4 votes
Need to solve this problem


4x(x2 + 2x - 2)=​

User Steve Bals
by
5.8k points

2 Answers

0 votes

Explanation:


4x( {x}^(2) + 2x - 2) \\ ( 4x * {x}^(2) ) + (4x * 2x) - (4x * 2) \\ {4x}^(3) + {8x}^(2) - 8x

HOPE IT HELPS ^_^

User Mithra Singam
by
5.5k points
5 votes

Answer:HEY THERE

Explanation:

4x(x2 + 2x - 2)

first multiply 4x and x2=4X^3

then multiply 4x and 2x =8X^2

then multiply 4x and -2 =-8x

=4X^3+8X^2-8X

THIS IS THE ANSWER HOPE THIS HELPS

User TheBen
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.